Hospital readmissions, mortality and potentially inappropriate prescribing: a retrospective study of older adults discharged from hospital. (22nd May 2018) - Counter, David; Millar, James W. T.; McLay, James S.
Abstract : Aims: Applying version 2 of the STOPP/START criteria to discharge prescriptions of older adults discharged from a general medical unit, the aim of this study is to assess potentially inappropriate medications (PIMs) and potential prescribing omissions (PPOs) and their association with hospital readmission and mortality. Methods: Discharge medications, co‐morbidities and patient demographics were recorded over an 8‐month period for consecutive emergency admissions of patients aged ≥65 years. PIMs and PPOs were identified using version 2 of the STOPP/START criteria. Multivariate analysis for association of PIMs and PPOs with re‐admissions and mortality during the follow‐up period were assessed using binary logistic regression. Results: Data for 259 patients with a mean age of 77 (65–99, 51% female) were analysed. At discharge, the mean number of co‐morbidities and medications per patient were 5.4 (SD: 2.1 range: 0–14) and 9.3 (SD: 4.0 range: 1–31) respectively. During the follow‐up period (mean 41.5 months, SD: 2.0 range: 38–46 months), 50.2% of patients had died and the median number of readmissions was two (IQR: 1–4 range: 0–33). Prescription of more than five medications was significantly associated with PIMs and PPOs (OR: 2.75, 95% CI: 1.34–5.62 and OR 3.20, 95% CI: 1.57–6.54 respectively). Presence of a PIM was associated with three or more readmissions (OR: 2.43 95% CI: 1.19–4.98) and PPOs with mortality (OR: 1.88, 95% CI: 1.09–3.27). Conclusions: Using version 2 of the STOPP/START criteria, the presence of PIMs and/or PPOs in older adults discharged from hospital is significantly associated with repeated hospital admissions and mortality respectively.